A wake-up call: from low prevalence to paediatric HIV crisis in Larkana, Pakistan - Khan, Muhammad Burhan; Khan, Attiya (Journal of the Pakistan Medical Association, 2025)
Dear Madam, Human Immunodeficiency Virus (HIV) is a retrovirus that attacks and damages the immune system, particularly the CD4+ T cells, resulting in acquired immunodeficiency syndrome (AIDS). It is a major public health issue, with having claimed of 40.4 million lives to date. In 2022, 630 000 people died globally from HIV-related causes. There were approximately 39.0 million people living with HIV by the end of 2022 with 1.3 million people becoming newly infected with HIV in 2022 globally.1 The prevalence of HIV in Pakistan is 0.1%, which is categorized as a low epidemic. Of the people living with HIV in the Eastern Mediterranean Region, 70% reside in three countries, including Pakistan. In 2016, 17,000 individuals lost their lives to AIDS, compared to 15,000 in 2014. This indicates a concerning rise in incidences and mortality in the general population, making it a significant issue that requires revaluation.2 HIV transmission occurs through the body fluids of an infected individual, including blood, breast milk, semen and vaginal fluids. Additionally, it can also spread from a mother to her baby.1 While the general prevalence of HIV in Pakistan remains relatively low, a worrying trend has emerged. In 2019, 30,191 individuals were tested for HIV in Larkana District, and 876 of them tested positive. Of those who tested positive, an alarming 719 (82%) were children under the age of 15. This issue was brought to the attention of the World Health Organization (WHO), who dispatched a team of health professionals to conduct a preliminary survey. The initial findings suggested that unsafe injection practices and poor infection control may be contributing to the high number of HIV infections among children. However, official results have yet to be confirmed. As of February 2021, Hermez et al reported that the outbreak in Larkana District is ongoing, with 1,492 cases diagnosed. Their study concluded that unsafe health practices were the primary cause of the outbreak of HIV among children. This conclusion was based on the finding that 99% of infected children had received injections in the past year, indicating the reuse of medical equipment and potentially contaminated blood transfusions as the primary cause of the outbreak.3 The situation in Larkana District, Pakistan, has raised serious concerns about the effectiveness of infection control measures in healthcare facilities and blood transfusion practices in the country. ---Continue